Integrating the Sustainable Development Goals into the strategy of higher education institutions - Leal Filho, W.; Simaens, A.; Paço, A.; Diaz, P. H.; de Vasconcelos, C. R. P.; Fritzen, B.; Maclean, C. (International Journal of Sustainable Development and World Ecology, 2023)
Despite the relevance of the UN Sustainable Development Goals (SDGs) and the fact that universities may make valuable contributions towards their implementation, there is a paucity of international studies which may allow an assessment of their degree of engagement or their performance against the SDGs. This paper reports on an international study among a sample of 128 members of higher education institutions (HEIs) located in 28 countries, which aimed at ascertaining the extent to which the SDGs are being integrated into the strategy of HEIs. The focus of this paper is on the means which have been deployed by various universities in order to embed or include the SDGs in their activities. More specifically, this paper explores 1) the scope of integration, 2) the organisational influences, and 3) strategic influencing factors. The research identified the fact that, whereas many organisations are aware of the need for and the relevance of sustainable development and consider it as part of their institutional settings, the same cannot be said for the SDGs, whose level of emphasis is that many HEIs are comparatively somewhat limited. In addition, there seems to be a shortage of training opportunities focusing on the SDGs, which could equip university staff to handle this topic. Against this background, the paper describes some measures that may be implemented to make the SDGs more present in HEI programmes, hence maximising their contribution to addressing the global sustainability challenges.